2020
DOI: 10.2174/1389557520666200509235945
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Strategies for Improving the Bioavailability of Inhaled Pharmaceutical Formulations

Abstract: : Pulmonary pharmaceutical formulations are targeted for the treatment of respiratory diseases. However, their application is limited due to physiological characteristics of the lungs such as branching structure, mucociliary and macrophages, as well as certain properties of the drugs like particle size and solubility. Nano-formulations can ameliorate particle sizes and improve drug solubility to enhance bioavailability in the lungs. The nano-formulations for lungs reviewed in this article can be classified int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 138 publications
0
7
0
Order By: Relevance
“…Several studies have shown that birds, poultry, and fish can ingest nanoparticles, then be absorbed by the digestive system and transferred from the circulatory system to different organs. 38,39 The accumulation of nano-to-micron-sized was detected in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that birds, poultry, and fish can ingest nanoparticles, then be absorbed by the digestive system and transferred from the circulatory system to different organs. 38,39 The accumulation of nano-to-micron-sized was detected in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Certain nanoformulations (i.e., dendrimers, polymers, liposomes, nano-emulsions, and micelles) can decrease particle sizes and have been used to increase bioavailability and minimize the adverse effects produced by the ligand(s) they deliver to the tumor site(s) [ 188 ]. The nanoformulations generally have a size range from 10 to 100 nm and can be classified as nanocarriers, no-carrier-added nanosuspensions and polymer-drug conjugates [ 189 ].…”
Section: Various Classes Of Nanomedicinesmentioning
confidence: 99%
“…The basal layer of the endothelium is referred to as the submucosa, which is rich in blood vessels and, therefore, facilitates the absorption of the vaccine antigens [ 8 ]. On the surface of the nasal cavity, the epithelial cells are tightly connected, forming a special physical barrier that prevents the invasion of antigenic particles, similar to the active defense against pathogenic microorganisms [ 9 ].…”
Section: Nasal Structure and Immune Responsesmentioning
confidence: 99%